Pengaruh Penerapan Program K3 terhadap Perilaku Pekerja dengan Sarana & Fasilitas Sebagai Variabel Intervening - I Nyoman Dana (Jurnal Syntax Transformation, 2021)
The high number of work accidents in the workplace, the fact that there is still weak attention to the value of OHS aspects in all work zones. Some research shows that there are workers who do not understand that they are unskilled and have a habit of unsafe behavior, there are workers who know how the work is carried out comfortably and safely, but are not supported by adequate work facilities, and there are some workers who feel that they are skilled. , but need direction and tutorials from those who understand better. For this reason, it is necessary to research and examine the effect of the implementation of the OHS program on the attitudes of workers in the work area viewed from several aspects. In addition, utilizing facilities and facilities as intervening variables to analyze the effect of facilities and facilities on worker behavior. The sampling method used Probability Sampling with Stratification Sampling procedure. Data analysis with the PLS-SEM procedure was used to describe the effect of the implementation of the OHS program on the behavior of workers with facilities and facilities as intervening variables. The conclusion of this research is that aspects of coaching & training, safety promotion and facilities & facilities have a significant effect on worker behavior. As well as aspects of inspection & audit as well as safety promotion also have a significant effect on facilities & facilities. Meanwhile, other aspects such as K3 policies & commitments and safety committees have no significant effect on worker behavior or on work facilities and facilities.